Preparation method of hexagonal boron nitride single crystal

By using 316 stainless steel alloy sheets as flux, combined with deoxygenation treatment and high-temperature growth methods, the problems of poor quality and small size of hexagonal boron nitride single crystals in the prior art are solved, and the preparation of high-purity and large-size hexagonal boron nitride single crystals are achieved.

CN119710889AActive Publication Date: 2025-03-28INST OF ENERGY HEFEI COMPREHENSIVE NAT SCI CENT (ANHUI ENERGY LAB)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411801317.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-28
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

It is difficult to prepare high-quality large-size single crystals of hexagonal boron nitride in the prior art, and the raw materials are highly toxic, making it inconvenient to control the reaction process.

Method used

Hexagonal boron nitride single crystals were prepared by deoxygenation and high-temperature growth methods using 316 stainless steel alloy sheets as flux, including pretreatment of hexagonal boron nitride powder, laying on stainless steel alloy sheets, high-temperature growth and annealing treatment, and finally peeling the single crystals with heat release tape.

Benefits of technology

A large-size hexagonal boron nitride single crystal with high purity and crack-free is achieved, which improves the quality and size of the single crystal, while avoiding the use of highly toxic raw materials, making it more convenient to control the reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710889A_ABST
    Figure CN119710889A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a hexagonal boron nitride single crystal material, and belongs to the technical field of hexagonal boron nitride single crystals. The preparation method of the hexagonal boron nitride single crystal material comprises the steps of raw material deoxidation, high-temperature growth, annealing treatment, single crystal stripping and the like, a stainless steel alloy sheet is adopted as a fluxing agent, more preferably, a 316 stainless steel alloy sheet is adopted, the 316 stainless steel alloy sheet contains rich element composition components, and the hexagonal boron nitride single crystal material is prepared. The growth quality of the hexagonal boron nitride single crystal material can be improved from all aspects, the high-quality and large-size single crystal material can be obtained, and in the high-temperature growth process, a sample is placed in a hexagonal boron nitride powder layer-stainless steel alloy sheet layer-hexagonal boron nitride powder layer placement mode, so that the yield of the hexagonal boron nitride single crystal material is improved. The contact area between powder and stainless steel alloy can be increased, and the effect of the stainless steel alloy sheet fluxing agent is exerted to the maximum extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hexagonal boron nitride single crystals, and particularly relates to a method for preparing a hexagonal boron nitride single crystal. Background Art

[0002] Hexagonal boron nitride is a semiconductor material that has isotopes 10 B, isotope 10 B can undergo nuclear reactions with neutrons to produce secondary charged particles with a certain amount of kinetic energy. These secondary charged particles will be transmitted within the hexagonal boron nitride and collide with the atoms in the lattice to produce a large number of electron-hole pairs. These electron-hole pairs can be separated by the electric field and collected by the electrodes. The collected signals can be characterized as detection signals of thermal neutrons. Using this property of hexagonal boron nitride crystals, many researchers are committed to the research of h-BN (hexagonal boron nitride) neutron detectors. In h-BN neutron detectors, neutron capture, charge collection, and electrical signal generation can occur in the same layer, thereby achieving direct detection of neutrons.

[0003] As an important component of h-BN neutron detectors, the quality of hexagonal boron nitride single crystals will directly affect the accuracy and quality of the obtained neutron detectors. At present, the main method for preparing hexagonal boron nitride single crystals is chemical vapor deposition. Most of these methods will select boron ammonia, trimethylamine boron, etc. as precursors, or select borane, boron chloride as boron source, ammonia or nitrogen as nitrogen source, and then obtain hexagonal boron nitride single crystals under high temperature or high pressure conditions. However, most of the raw materials used in this method are highly toxic, which is not conducive to safe production and control of the reaction process.

[0004] Another method for preparing hexagonal boron nitride single crystals is the metal flux method. Compared with the chemical vapor deposition method, the raw material of the metal flux method is hexagonal boron nitride powder, which is safe and non-toxic, and easier to control than gas raw materials. However, the hexagonal boron nitride single crystals obtained by the metal flux method are small in size, the quality of single crystal growth is poor, and cracks exist. Therefore, a safe and easy-to-control method for preparing large-sized hexagonal boron nitride single crystals is urgently needed. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a hexagonal boron nitride single crystal material, so as to solve the problems of poor quality, poor performance and small size of the hexagonal boron nitride single crystal material obtained by the existing preparation method.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] The present invention provides a method for preparing a hexagonal boron nitride single crystal material, comprising the following steps:

[0008] S1. Clean and dry the stainless steel alloy sheet;

[0009] S2. The hexagonal boron nitride powder and the boron nitride crucible boat are deoxidized together to obtain a pretreated hexagonal boron nitride powder;

[0010] S3. The pretreated hexagonal boron nitride powder is spread in a boron nitride crucible boat, covered with a stainless steel alloy sheet, and then a layer of pretreated hexagonal boron nitride powder is evenly spread on the stainless steel alloy sheet, and finally the lid of the boron nitride crucible boat is covered to obtain a sample to be processed;

[0011] S4. The sample obtained in step S3 is placed in a tube furnace, and the air in the furnace is first evacuated to remove the air, and then nitrogen is introduced to normal pressure, and the sample is grown at high temperature for 10 to 12 hours under a nitrogen flow, and then the temperature is reduced to 900 to 1000° C. and the heating is stopped, and the sample is naturally cooled to room temperature to obtain a crude single crystal of hexagonal boron nitride grown on the surface of the stainless steel alloy;

[0012] S5. annealing the crude hexagonal boron nitride single crystal to obtain a hexagonal boron nitride single crystal;

[0013] S6. Use thermal release tape to peel off the hexagonal boron nitride single crystal on the surface of the stainless steel alloy to obtain the hexagonal boron nitride single crystal material.

[0014] Preferably, the stainless steel alloy sheet is a 316 stainless steel alloy sheet; the 316 stainless steel alloy sheet includes the following components: 0.08-0.1% carbon, 1.5-2.0% manganese, 1-1.5% silicon, 0.04-0.045% phosphorus, 0.03-0.04% sulfur, 16.0-21.0% chromium, 9.0-12.0% nickel and 2.0-3.0% molybdenum.

[0015] Preferably, the purity of the hexagonal boron nitride powder is ≥99.9%, and the particle size is 1 to 3 μm.

[0016] Preferably, the deoxidation treatment is carried out under a nitrogen flow of 100 to 120 sccm; the deoxidation treatment temperature is 1350 to 1450° C., and the deoxidation treatment time is 10 to 12 hours.

[0017] Preferably, the mass ratio of the pretreated hexagonal boron nitride powder to the stainless steel alloy sheet is 1:(10-14).

[0018] More preferably, the mass ratio of the pretreated hexagonal boron nitride powder to the stainless steel alloy sheet is 1:12.

[0019] Preferably, the mass ratio of the two layers of pretreated hexagonal boron nitride powder located above and below the stainless steel alloy sheet is (0.5-0.6):(0.4-0.5).

[0020] More preferably, the mass ratio of the two layers of pre-treated hexagonal boron nitride powder located above and below the stainless steel alloy sheet is 0.5:0.5.

[0021] Preferably, the nitrogen gas flow rate in step S4 is 100-200 sccm.

[0022] Preferably, the heating rate of the high temperature growth is 10-15°C / min; the high temperature growth temperature is 1300-1400°C.

[0023] Preferably, the cooling rate in step S4 is 5 to 10° C. / min.

[0024] Preferably, the annealing temperature is 1100-1200° C., and the annealing time is 2-3 hours.

[0025] Preferably, the heat release temperature of the heat release tape is 90-100°C.

[0026] Beneficial effects of the present invention:

[0027] 1. The hexagonal boron nitride single crystal material of the present invention is first deoxidized before preparation. Since the hexagonal boron nitride powder purchased conventionally will inevitably contain oxygen elements, the presence of these oxygen atoms will react with boron or nitrogen during the subsequent high-temperature growth process, thereby affecting the formation of the single crystal structure and causing the appearance of by-products. After deoxidation, the carried oxygen and moisture can be prevented from affecting the growth of the single crystal, thereby reducing unnecessary phase changes or the generation of by-products during the growth process, and helping to obtain a hexagonal boron nitride single crystal material with higher purity and better quality. In addition, during the deoxidation process, the loading tool for subsequent high-temperature growth, i.e., the boron nitride crucible boat, is also deoxidized. On the one hand, the mechanical strength and thermal stability of the boron nitride crucible boat can be improved to a certain extent, and on the other hand, trace oxygen and impurity elements can be effectively prevented from being mixed into the sample, thereby contaminating the obtained hexagonal boron nitride single crystal or changing the chemical composition of the single crystal, and reducing the interference of the tool on the formation of the single crystal.

[0028] 2. In the present invention, 316 stainless steel alloy sheet is used as a flux for the formation of hexagonal boron nitride single crystal. Compared with general single metal flux or some alloy flux, the flux raw material of the present invention is easy to obtain, and the 316 stainless steel alloy sheet contains rich metal components, which can improve the growth quality of single crystal at different levels. In particular, compared with other alloy materials, 316 stainless steel alloy has a relatively high proportion of chromium elements, and the large proportion of nickel-chromium components can improve the solubility of nitrogen in the alloy, and the present invention finds that molybdenum can also increase the solubility of nitrogen, and nitrogen is an essential element for the growth of hexagonal boron nitride single crystals. The increase in solubility will significantly promote the growth of single crystals, and nickel also has a certain catalytic effect, which can guide the growth of hexagonal boron nitride single crystals. Moreover, although the high-temperature growth of the present invention is carried out under the condition of removing air and nitrogen gas flow, it is difficult to achieve absolute vacuum and absolute deoxidation of materials, and 316 stainless steel alloy contains a small amount of carbon, and these carbon atoms can help absorb oxygen and moisture during high-temperature growth, which is conducive to the growth of single crystals. Compared with direct doping of carbon powder, the present invention does not require additional addition of substances, which is beneficial to substance separation and improves the purity and quality of single crystals.

[0029] 3. In the preparation of the sample of the present invention, a layer of pretreated hexagonal boron nitride powder is first laid, then covered with a stainless steel alloy sheet, and finally another layer of pretreated hexagonal boron nitride powder is laid flat. This special raw material placement setting can maximize the contact area between the hexagonal boron nitride powder and the stainless steel alloy sheet, and can also better improve the heat transfer efficiency, so that the raw material can be heated evenly, and at the same time can grow evenly on the surface of the stainless steel alloy, increase the size of the formed single crystal, and better reduce the occurrence of cracks.

[0030] 4. After high-temperature growth, the hexagonal boron nitride single crystal is prone to accumulation of thermal stress at the interface between the two phases due to the mismatch in thermal expansion coefficients between boron nitride and the stainless steel alloy. After cooling, this stress easily causes cracks or other defects in the single crystal, affecting the quality of the single crystal. Therefore, the present invention also performs annealing treatment on the hexagonal boron nitride single crystal after growth, which can not only eliminate stress and reduce defects and damage caused by stress, but also help promote atomic rearrangement, making the obtained single crystal crystal structure more orderly and perfect, thereby improving the ductility, crystallinity and stability of the obtained single crystal material, and facilitating peeling from the stainless steel alloy.

[0031] 5. The present invention uses a thermal release tape to peel off the hexagonal boron nitride single crystal material grown on the surface of the stainless steel alloy, so that a single crystal material with a larger size and better quality can be obtained more completely, and the damage and loss of the single crystal caused during the peeling process can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The present invention will be further described below in conjunction with the accompanying drawings.

[0033] Figure 1 is a schematic diagram of a flow chart of Embodiment 1 of the present invention;

[0034] Figure 2 1 is a schematic diagram of the structure of the raw material placement of Example 1 of the present invention; wherein 1 is a boron nitride crucible boat, 2 is a pre-treated hexagonal boron nitride powder layer, and 3 is a 316 stainless steel alloy sheet;

[0035] Figure 3 It is the Fourier transform infrared spectrum diagram of Example 1 of the present invention. DETAILED DESCRIPTION

[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Example

[0038] Example 1: A hexagonal boron nitride single crystal material is prepared according to the following method:

[0039] S1. Take a piece of 316 stainless steel alloy sheet, the mass of 316 stainless steel alloy sheet is 180g, wash it with deionized water and ethanol, and then dry it for use;

[0040] S2. The hexagonal boron nitride powder was placed in a boron nitride crucible boat, and then placed in a tubular furnace. The furnace tube was evacuated to a vacuum state using a vacuum pump, and then nitrogen was introduced to the furnace to a normal pressure state. Then, under a nitrogen flow of 100 sccm, the temperature was increased to 1400°C at a heating rate of 10°C / min, and the mixture was kept at this temperature for 12 hours, and then naturally cooled to room temperature for deoxidation treatment to obtain a pretreated hexagonal boron nitride powder;

[0041] S3. Take 15g of pretreated hexagonal boron nitride powder, spread the pretreated hexagonal boron nitride powder in a boron nitride crucible boat, cover it with the 316 stainless steel alloy sheet dried in step S1, and then evenly spread a layer of pretreated hexagonal boron nitride powder on the 316 stainless steel alloy sheet, wherein the mass ratio of the two layers of pretreated hexagonal boron nitride powder located above and below the 316 stainless steel alloy sheet is 0.5:0.5, and finally cover the lid of the boron nitride crucible boat to obtain a sample to be processed;

[0042] S4. Place the sample obtained in step S3 in a tube furnace, first evacuate the air in the furnace, then introduce nitrogen to normal pressure, raise the temperature to 1300°C at a heating rate of 10°C / min under a nitrogen flow of 100 sccm, and keep it for high-temperature growth for a total of 10 hours, then lower the temperature to 1000°C at a cooling rate of 5°C / min, stop heating, and naturally cool to room temperature to obtain a crude hexagonal boron nitride single crystal grown on the surface of the stainless steel alloy;

[0043] S5. The crude hexagonal boron nitride single crystal obtained above was annealed by heating to 1200°C at a rate of 10°C / min, and then naturally cooled to room temperature after being kept for 2h to obtain a hexagonal boron nitride single crystal;

[0044] S6. Use a thermal release tape to peel off the hexagonal boron nitride single crystal on the surface of the stainless steel alloy to obtain a hexagonal boron nitride single crystal material, wherein the thermal release temperature of the thermal release tape is 100° C. and the tape area is 20 mm×20 mm.

[0045] pass Figure 3 , it can be seen that at 780.2cm -1 and 1375cm -1 The two main spectral bands nearby are mainly BNB bending vibration and BN stretching vibration, which are typical characteristics of hexagonal boron nitride, and the obtained peaks are clear and free of impurity peaks, indicating that the material prepared by the present invention is high-purity hexagonal h-BN. And after observation, the obtained single crystal material has good morphology, good crystallinity, no cracks, large size, and the side length of the single crystal can reach hundreds of microns.

[0046] Example 2, a hexagonal boron nitride single crystal material, is different from Example 1 only in that the amount of pre-treated hexagonal boron nitride powder added is 13 g. Finally, a large-sized hexagonal boron nitride single crystal material with good crystallinity and no cracks is obtained.

[0047] Example 3, a hexagonal boron nitride single crystal material, is different from Example 1 only in that the amount of pre-treated hexagonal boron nitride powder added is 18g. Finally, a large-sized hexagonal boron nitride single crystal material with good crystallinity and no cracks is obtained.

[0048] Example 4, a hexagonal boron nitride single crystal material, is different from Example 1 only in that the amount of pre-treated hexagonal boron nitride powder added is 10 g. Finally, a large-sized hexagonal boron nitride single crystal material with good crystallinity and no cracks is obtained.

[0049] Example 5, a hexagonal boron nitride single crystal material, the only difference from Example 1 is that the mass ratio of the two layers of pre-treated hexagonal boron nitride powder located above and below the 316 stainless steel alloy sheet is 0.6:0.4. Finally, a large-sized hexagonal boron nitride single crystal material with good crystallinity and no cracks is obtained.

[0050] Example 6, a hexagonal boron nitride single crystal material, is different from Example 1 only in that the mass ratio of the two layers of pre-treated hexagonal boron nitride powder located above and below the 316 stainless steel alloy sheet is 0.4:0.6.

[0051] Compared with the single crystal material obtained in Example 1, there are fine cracks, and after the single crystal grows on the stainless steel surface, it is difficult to peel it off using a thermal release tape due to its small size and thin thickness, and the proportion of single crystal materials with perfect morphology removed is reduced. In addition, part of the powder under the stainless steel alloy sheet cannot form crystals on the stainless steel alloy surface, resulting in a decrease in the crystallization rate.

[0052] Comparative Example

[0053] Comparative Example 1 is a hexagonal boron nitride single crystal material, which is different from Example 1 only in that an equal amount of single nickel sheet is used to replace the 316 stainless steel alloy sheet. The hexagonal boron nitride single crystal material obtained at last is small in size, difficult to peel off, and has fine cracks in the single crystal material.

[0054] Comparative Example 2, a hexagonal boron nitride single crystal material, is different from Example 1 only in that the crude hexagonal boron nitride single crystal product grown on the surface of the stainless steel alloy obtained after high-temperature growth treatment is not annealed, and the single crystal material is directly peeled off using a thermal release tape. The hexagonal boron nitride single crystal material finally obtained has poor crystallinity, and cracks appear on the surface and inside of the material.

[0055] Comparative Example 3, a hexagonal boron nitride single crystal material, is different from Example 1 only in that the hexagonal boron nitride powder and the boron nitride crucible boat are not subjected to deoxidation treatment. Finally, only a small amount of hexagonal boron nitride single crystal material grows on the surface of the stainless steel alloy, and the formed single crystal material has many cracks and is small in size.

[0056] Comparative Example 4, a hexagonal boron nitride single crystal material, is different from Example 1 only in that S3 is performed according to the following steps:

[0057] Take 15g of pretreated hexagonal boron nitride powder, spread it in a boron nitride crucible boat, cover it with the 316 stainless steel alloy sheet dried in step S1, and finally cover the lid of the boron nitride crucible boat to obtain a sample to be processed. Finally, only part of the hexagonal boron nitride single crystal material is formed on the surface of the stainless steel alloy, and the formed single crystal material has poor crystallinity, cracks, and uneven single crystal size, and there are differences in size.

[0058] Comparative Example 5, a hexagonal boron nitride single crystal material, is different from Example 1 only in that S3 is performed according to the following steps:

[0059] The 316 stainless steel alloy sheet dried and prepared in step S1 was placed in a boron nitride crucible boat, and then 15 g of pre-treated hexagonal boron nitride powder was taken, and a layer of pre-treated hexagonal boron nitride powder was spread on the 316 stainless steel alloy sheet, and finally the lid of the boron nitride crucible boat was covered to obtain a sample to be processed. The crystallization rate of the hexagonal boron nitride single crystal material obtained at last decreased, the crystallization performance decreased, and cracks existed in some single crystal materials.

[0060] Comparative Example 6, a hexagonal boron nitride single crystal material, is different from Example 1 only in that S3 is performed according to the following steps:

[0061] Take 15g of pretreated hexagonal boron nitride powder, add 15g of pretreated hexagonal boron nitride powder and 316 stainless steel alloy particles (average particle size of 50μm) into a boron nitride crucible boat, and finally cover the lid of the boron nitride crucible boat to obtain a sample to be processed. The hexagonal boron nitride single crystal material finally obtained is small in size, the side length of the single crystal ranges from a few microns to tens of microns, the size is uneven, and the crystallinity is poor, and the obtained single crystal material has partial cracks.

[0062] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0063] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a hexagonal boron nitride single crystal material, characterized in that: The following steps are involved: S1. Clean the stainless steel alloy sheet and dry it for later use; S2. The hexagonal boron nitride powder and the boron nitride crucible boat are deoxidized together to obtain a pretreated hexagonal boron nitride powder; S3. The pretreated hexagonal boron nitride powder is spread in a boron nitride crucible boat, covered with a stainless steel alloy sheet, and then a layer of pretreated hexagonal boron nitride powder is evenly spread on the stainless steel alloy sheet, and finally the lid of the boron nitride crucible boat is covered to obtain a sample to be processed; S4. The sample obtained in step S3 is placed in a tube furnace, and the air in the furnace is first evacuated to remove the air, and then nitrogen is introduced to normal pressure, and the sample is grown at high temperature for 10 to 12 hours under a nitrogen flow, and then the temperature is reduced to 900 to 1000° C. and the heating is stopped, and the sample is naturally cooled to room temperature to obtain a crude single crystal of hexagonal boron nitride grown on the surface of the stainless steel alloy; S5. annealing the crude hexagonal boron nitride single crystal to obtain a hexagonal boron nitride single crystal; S6. Use thermal release tape to peel off the hexagonal boron nitride single crystal on the surface of the stainless steel alloy to obtain the hexagonal boron nitride single crystal material.

2. The method for preparing hexagonal boron nitride single crystal material according to claim 1, characterized in that: The stainless steel alloy sheet is a 316 stainless steel alloy sheet; the 316 stainless steel alloy sheet includes the following components: 0.08-0.1% carbon, 1.5-2.0% manganese, 1-1.5% silicon, 0.04-0.045% phosphorus, 0.03-0.04% sulfur, 16.0-21.0% chromium, 9.0-12.0% nickel and 2.0-3.0% molybdenum.

3. The method for preparing hexagonal boron nitride single crystal material according to claim 1, characterized in that: The purity of the hexagonal boron nitride powder is ≥99.9%, and the particle size is 1-3 μm.

4. The method for preparing hexagonal boron nitride single crystal material according to claim 1, characterized in that: The deoxidation treatment is carried out under a nitrogen flow of 100 to 120 sccm; the deoxidation treatment temperature is 1350 to 1450° C., and the deoxidation treatment time is 10 to 12 hours.

5. The method for preparing hexagonal boron nitride single crystal material according to claim 1, characterized in that: The mass ratio of the pretreated hexagonal boron nitride powder to the stainless steel alloy sheet is 1:(10-14).

6. The method for preparing hexagonal boron nitride single crystal material according to claim 1, characterized in that: The mass ratio of the two layers of pre-treated hexagonal boron nitride powder located above and below the stainless steel alloy sheet is (0.5-0.6): (0.4-0.5).

7. The method for preparing hexagonal boron nitride single crystal material according to claim 1, characterized in that: The nitrogen gas flow rate in the step S4 is 100-200 sccm.

8. The method for preparing hexagonal boron nitride single crystal material according to claim 1, characterized in that: The heating rate of the high temperature growth is 10-15°C / min; the high temperature growth temperature is 1300-1400°C.

9. The method for preparing hexagonal boron nitride single crystal material according to claim 1, characterized in that: The annealing temperature is 1100-1200° C., and the annealing time is 2-3 hours.

10. The method for preparing hexagonal boron nitride single crystal material according to claim 1, characterized in that: The heat release temperature of the heat release tape is 90-100°C.

Citation Information

Patent Citations

  • Preparation method of large-sized hexagonal boron nitride monocrystals

    CN109695053A

  • Growth method of centimeter-sized hexagonal boron nitride single crystal

    CN113417002A

  • Method for preparing hexagonal boron nitride single crystal

    CN115491747A